Synthesis, characterization and H2 adsorption performances of polymeric Co(II) and Ni(II) complexes of pyrazine-2,3-dicarboxylic acid and 1-vinylimidazole - Andac, Omer; Gorduk, Semih; Yilmaz, Hakan (SPRINGER, 2018)
We studied the synthesis and characterization of polymeric coordination complexes of Co(II) and Ni(II) ions with pyrazine-2,3-dicarboxylic acid and 1-vinylimidazole. The e lemental analysis, infrared spectroscopy, powder X-ray diffraction, magnetic susceptibility, thermal analysis and X-ray single crystal techniques were used in the characterization. The X-ray single crystal analysis suggests that the pyrazine-2,3-dicarboxylato ligand acts as a bridging ligand through the oxygen atoms of the carboxylate groups and the nitrogen atoms on the pyrazine ring. The 1-vinylimidazole ligand behaves as a monodentate ligand via the ring nitrogen atom. Further, the H-2 adsorption studies were carried out at 75 K for various increasing pressures and the highest H-2 adsorption performances for Co(II) and Ni(II) complexes were estimated as 2.66 and 2.99 wt% at 87 bar. The theoretical calculations using the crystal data were also performed to determine the voids in the structure of Co(II) complex.
Keywords: Pyrazine-2,3-dicarboxylic acid; 1-Vinylimidazole; Polymeric complex; Bridging ligand; H-2 adsorption; METAL-ORGANIC FRAMEWORKS; N-DONOR LIGANDS; COORDINATION POLYMERS; HYDROGEN STORAGE; MOLECULAR SIMULATIONS; STRUCTURAL-CHARACTERIZATION; MAGNETIC-PROPERTIES; CRYSTAL-STRUCTURES; CU(II) COMPLEXES; SQUARIC ACID; Chemistry